Development of Balance Performance Norms for the Biodex Balance System. - Finn, Joan (1997)
Keywords: dept.hms; faculty_collection; sabbatical_report

The effect of upper trapezius taping on electromyographic activity in the upper and middle trapezius region - Morin, G.E.; Tiberio, D.; Austin, G. (Journal of Sport Rehabilitation, 1997)
A characteristic of scapulothoracic dysfunction is the tendency for the upper regions of the trapezius to hypertrophy in relation to its middle and lower portions. This creates a muscular imbalance that can alter scapular position and subsequently the length-tension relationship of the shoulder muscles. Tape was applied over the right upper trapezius to inhibit electrical activity in the muscles of 10 uninjured subjects. EMG activity was recorded in two locations of the upper trapezius and one location in the middle to lower trapezius region while each subject maintained an isometric contraction designed to activate both muscles. With the tape applied, there was a statistically significant reduction in EMG activity of the upper trapezius with a corresponding increase in the middle/lower trapezius. The ability of the tape to alter trapezius activity in this fashion may help correct muscular imbalances in the trapezius muscle.
23 citations (Crossref) [2023-10-31]
Keywords: article; controlled study; dept.hms; electromyography; human; human experiment; muscle isometric contraction; normal human; scapula; shoulder pain; trapezius muscle

Effects of isokinetic training, detraining, and retraining on knee strength measures among active elderly persons - Jett, RE; Axtell, RS; Finn, JA (Journal of Aging and Physical Activity, 1997)
tex.eissn: 1543-267X tex.unique-id: ISI:A1997XY03300025
Keywords: dept.hms; ⛔ No DOI found